1986
DOI: 10.1007/bf02638229
|View full text |Cite
|
Sign up to set email alerts
|

A simple chemical method for stabilization of rice bran

Abstract: A new simple chemical method for stabilization of rice bran is described. The process, based on the principle that lipase activity will be low at low pH, uses hydrochloric acid at 40 l/ton of bran for lowering the pH of rice bran from 6.9-6.0 to 4.0. The acid can be applied easily by sprinkling or spraying. The operation on small lots can be done by hand mixing of bran, but it is more efficient and effective if mechanical mixing, like a rotary or a trough mixer, is used. This simple method, which takes less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 1 publication
6
39
0
Order By: Relevance
“…There was no significant increase in free fatty acid content of chemically treated bran during the entire storage. Prabhakar and Venkatesh (1986) reported similar results working with acid treated brans. According to Kaur et al (2011) free fatty acids (%) for enriched pasta increased with storage period, but the values remained in the acceptable range because of which, the taste, flavour and acceptability of pasta was not much affected.…”
Section: Moisture Contentsupporting
confidence: 60%
“…There was no significant increase in free fatty acid content of chemically treated bran during the entire storage. Prabhakar and Venkatesh (1986) reported similar results working with acid treated brans. According to Kaur et al (2011) free fatty acids (%) for enriched pasta increased with storage period, but the values remained in the acceptable range because of which, the taste, flavour and acceptability of pasta was not much affected.…”
Section: Moisture Contentsupporting
confidence: 60%
“…The methods employed to stabilize the bran (prevention of rancidity by lipase action) are based on reducing the moisture content, or altering the temperature or pH to destroy the activity of lipase. 30 These include processes involving heat treatment, cold storage, 30 chemical treatment, control of relative humidity during storage and simultaneous milling and extraction of the oil. 31,32 Hydrochloric acid treatment has been successfully used to stabilize rice bran.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Hydrochloric acid treatment has been successfully used to stabilize rice bran. 30 When rice bran is subjected to a short-term, high-temperature treatment immediately after milling, the lipase activity is destroyed, thereby stabilizing the bran. 33 However, such heat processing of the bran denatures native proteins, and also affects the vitamins.…”
Section: Resultsmentioning
confidence: 99%
“…Research in the last decades showed that rice bran is an outstanding source of vitamins, minerals, antioxidants, proteins, fats and dietary fibers [8]. Several problems of raw bran management have restricted production of edible grade rice bran oil.…”
Section: Introductionmentioning
confidence: 99%